2019
DOI: 10.1021/acs.jpca.9b05534
|View full text |Cite
|
Sign up to set email alerts
|

Structural Effects on the Norrish Type I α-Bond Cleavage of Tropospherically Important Carbonyls

Abstract: Norrish Type I (NTI) α-bond cleavage is the dominant photolysis mechanism in small carbonyls and is an important source of radicals in the troposphere. In nonsymmetric species two cleavages are possible, NTIa and NTIb, forming larger and smaller alkyl radicals, respectively. For a data set of 20 small, atmospherically relevant carbonyls we predict NTIa and NTIb thresholds on the S 0 , S 1 , and T 1 electronic states. The calculated NTIa T 1 thresholds give a mean absolute deviation (MAD) of 5.8 kJ/mol with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 162 publications
3
47
0
Order By: Relevance
“…The computational protocols used in this paper to study S 1 , T 1 , and S 0 NTII photolysis thresholds are largely the same as reported by the authors in an earlier publication on the NTI reaction in carbonyls. 49 Photolysis thresholds are calculated by the addition of the intrinsic reaction barrier (relative to the relevant electronic state minimum) to the 0-0 excitation energy (from the S 0 minimum to the excited state minimum). The 0-0 excitation energies used here are calculated using protocol detailed by the authors in an earlier paper studying carbonyl excitation energies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The computational protocols used in this paper to study S 1 , T 1 , and S 0 NTII photolysis thresholds are largely the same as reported by the authors in an earlier publication on the NTI reaction in carbonyls. 49 Photolysis thresholds are calculated by the addition of the intrinsic reaction barrier (relative to the relevant electronic state minimum) to the 0-0 excitation energy (from the S 0 minimum to the excited state minimum). The 0-0 excitation energies used here are calculated using protocol detailed by the authors in an earlier paper studying carbonyl excitation energies.…”
Section: Methodsmentioning
confidence: 99%
“…48 Butyrophenone has a phenyl group conjugated with the C O moiety and as an aromatic carbonyls it has similarities to the α, β-unsaturated carbonyls discussed here. This includes a T 2 state that is energetically accessible at tropospheric photon energies, 49 as well as a S 1 /T 2 /T 1 three-state intersection. This intersection is not at configurations accessed by the triplet biradical, and does not intersect with S 0 , and so does not decrease the triplet biradical lifetime.…”
Section: Early Electronic Structure Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The error spread can be significantly reduced by using more accurate methods for E vert . A simple composite scheme was used in previous work by the authors, 1 where E vert is replaced with an inexpensive EOM-CC method (STEOM) and all other quantities were calculated with (TD-)DFT. This procedure (columns 3 and 4 in Figure 3) significantly decreases the error distribution, regardless of whether CAM-B3LYP or B3LYP is used.…”
Section: S 1 Relaxation Energies -E Relaxmentioning
confidence: 99%
“…We have previously identified 20 small carbonyl species that are relevant to tropospheric chemistry and for which experimental data is available. 1 Here, we add an additional 18 larger carbonyl species that require an affordable protocol for theoretical calculation of their excitation energies to be viable. The states of interest here for carbonyls are the ground and excited singlet states (S 0 and S 1 respectively), since direct transition from the ground state to the triplet state (S 0 → T 1 ) is spin-forbidden in the n → π * excitation.…”
Section: Introductionmentioning
confidence: 99%